Persistent Kruppel-like factor 4 expression predicts progression and poor prognosis of head and neck squamous cell carcinoma - Tai, Shyh‐Kuan; Yang, Muh‐Hwa; Chang, Shyue‐Yih; Chang, Yung‐Chi; Li, Wing‐Yin; Tsai, Tung‐Lung; Wang, Yi‐Fen; Chu, Pen‐Yuan; Hsieh, Shie‐Liang (Cancer science, 2011)
Head and neck squamous cell carcinoma (HNSCC) is one prevalent human cancer worldwide. No molecular markers are presently used for predicting prognosis in HNSCC. Krüppel‐like factor 4 (KLF4) is a transcription factor with diverse physiological functions, and possesses opposing roles in different human cancers. The expression and roles of KLF4 in HNSCC remain to be elucidated. In this study, immunohistochemical (IHC) analysis of KLF4 in 62 HNSCC was firstly performed. IHC results demonstrated that 42 (67.7%) had decreased KLF4 expression compared with surrounding normal epithelium, while persistent KLF4 expression was demonstrated in 20 (32.3%). The IHC results were further verified by Western blot and real‐time PCR analyses to confirm the robustness of staining and interpretation. Interestingly, persistent KLF4 expression independently correlated with a worse disease‐specific survival (P = 0.005), especially in patients with advanced disease. In consistent with clinical observation, all five HNSCC cell lines tested revealed a low level of baseline KLF4 expression. Moreover, enforced KLF4 expression in cell line SAS significantly increased in vitro migration/invasion abilities, multi‐drug resistance, and in vivo tumorigenicity. These results clearly illustrate that persistent KLF4 expression predicts poor prognosis and confers aggressiveness in HNSCC. Our data therefore provides valuable information that HNSCC with persistent KLF4 expression might require intensified combination treatment in future practice. (Cancer Sci 2011; 102: 895–902)